Pemanfaatan Batu Gunung Tambolang Kabupaten Toraja Utara Pada Campuran Laston AC-BC - Gideon Rante; Alpius; Sufiati Bestari (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This research was conducted to determine the aggregate characteristic value, the AC-BC mixture design, and the Marshall stability value of the remaining AC-BC mixture design through the Conventional Marshall and Marshall Immersion testing with reference to the 2018 General specifications (Division 6) of the Ministry of PubIic Works and PubIic Housing of the RepubIic of lndonesia. and SNI Testing Standards. Before designing the composition for Conventional Marshall testing and making test specimens to obtain residual Marshall stability, the first thing to do is test the characteristics of coarse aggregate, fine aggregate, and asphalt (filler).The results of this study indicate that the material from Mount Tambolang Toraja Utara fulfills the requirements set in the 2018 General Highways specification. Based on the composition of the AC-BC mixture using material from Mount Tambolang, namely coarse aggregate 42.82%, fine aggregate 45 , 73%, filler material 5.45%, with an optimum aspaI content of 6%. After doing the Conventional Marshall test, the results obtained, the test meets the specifications on testing flow, stability, VMA, VIM and VFB. While the remaining Marshall stability using material from Mount Tambolang, North Toraja District, meets the requirements of the 2018 General Bina Marga Specifications, namely 96.29%> 90%.